266 MEMBRANOUS (CLASS V) RENAL DISEASE IN SYSTEMIC LUPUS ERYTHEMATOSUS MAY BE MORE COMMON THAN PREVIOUSLY REPORTED: RESULTS OF A 3-YEAR RETROSPECTIVE ANALYSIS. (10th December 2015) - Bhinder, S. K.; Brar, H. S.; Majithia, V.; Lebrun, C.
Abstract : Background: Renal involvement in systemic lupus erythematosus (SLE) is characterized into 6 histological classes per WHO classification. The actual incidence and prevalence of the various classes are not known, but appear to vary with gender, age and ethnicity. Class IV is the most common renal pathology, and the incidence of membranous (class V) has been reported to be 10-20%. We retrospectively analyzed renal biopsies in SLE patients done in our institution over last 3 years and hereby report our initial experience. Methods: The renal biopsies on SLE patients over past three years (Jan 2002- July 2004) in our institution were evaluated. The patient records were further reviewed for the age at the time of biopsy, sex, and race and detailed information was then obtained for the patients with class V lupus nephritis. Results: There were a total of 57 SLE patients who had renal biopsy from Jan 2002-July 2004. 54 of these patients had single biopsy and 3 patients had multiple biopsies. There were 47 females, 10 males, 53 African-Americans (AA), and 4 whites. Out of the 54 patients with a single biopsy, 23 (42.5%) had isolated class V disease, 20 (37.03%) had class IV, 5 (9.2%) had class II, 3 (5.5%) had class VI and III, and none had class I. The prevalence of these classes was similar in both sexes. 19 out of 23 patients with class V had not received any immunosuppressive therapy or high dose steroids prior to biopsy. 70% of the patients with class V lupus nephritis had nephrotic range proteinuria and 30% had non-nephrotic range proteinuria. Conclusion: In contrast to previously reported literature, isolated membranous (class V) disease was much more prevalent in this series: 42% vs. 10-20%. In addition, AA race and male sex were not found to be associated with a more severe renal disease (class IV). More than 90% of patients in this series were of AA ethnicity, and class V disease was as prevalent in males as in females (40% vs. 43%). The predominance of class V renal disease may reflect earlier diagnosis and referral of SLE patients with renal disease. Also patients with a more severe presentation might have progressed to end-stage renal disease and were never referred to the university, reflecting a referral bias. It is also postulated that use of immunosuppressive agents may change the renal pathology, but most of our patients with class V disease had not received these agents prior to biopsy. Although this is a small series, it does raise questions about epidemiology of renal disease in SLE. We recommend future studies to further elucidate the findings in this case series.